Effect of Mixing Temperature of CMP Pulp and Cellulose Nanofiber on Paper Properties - Sahba Alinia (Iranian Journal of Wood and Paper Industries, 2013)
Several processing parameters affect the function of cellulose nanofiber as an environmentally friend cellulosic reinforcer. One of the potential parameters can be the mixing temperature of pulp and cellulose nanofiber that has been investigated in this study. In order to study the influence of this parameter, mixing drainage velocity and the air permeability and strength properties of resulting paper were measured. A mixture of chemi-mechanical pulp suspensions (with concentration of 0.2 wt% and freeness of 250 ml, CSF) containing 5 wt% cellulose nanofiber were prepared. This mixture was then stirred at 25, 50, and 70 ◦C using a magnetic stirrer for 1 hour followed by draining using vacuum filtration to make wet handsheet. The wet handsheet was first pressed, and then dried in oven at 100 ◦C for 24 hours. The test’ results showed that the increase of mixing temperature led to decreasing drainage time and air permeability. The strength properties of paper reinforced by nanofibers were positively affected by mixing temperature (i.e. the more mixing temperature, the higher strength). The data of tensile strength index was considerably increased. The tear strength of paper increased approximately by 200% over rising mixing temperature.